Fluorescent imaging in living systems. - Emptage, N (2001)
The use of fluorescent imaging techniques in the study of living biological systems has become an important experimental tool in modern biology. Over recent years novel imaging technologies have been developed and older techniques refined. New fluorescent probes continue to become available and the ways in which they are used is increasingly creative. Commonly used imaging methods such as confocal and multiphoton microscopy, when combined with techniques such as fluorescence resonance energy transfer (FRET) and fluorescence lifetime imaging (FLIM), can provide powerful strategies with which to study molecular events in intact cells.